Case Report: False aneurysm as a late unusual complication of the aortofemoral bypass graft in a patient with critical leg ischemic symptoms: interesting case - Belfiore, M. P.; Zeccolini, R.; Roccatagliata, P.; Gallo, L.; Fabozzi, A.; Cappabianca, S. (Frontiers in Radiology, 2024)
The contents of our manuscript are well-aligned with the scope of the selected journal and specialty. This manuscript discusses a case report involving an 82-year-old male who developed a pseudoaneurysm after aorto-bifemoral bypass surgery, a procedure commonly used for aortoiliac occlusive disease. The manuscript emphasizes the importance of diagnostic imaging techniques, such as Duplex ultrasound and Computed Tomography-angiography (PSA), in the early detection and management of pseudoaneurysms(PSAs). It also highlights the rarity and potential severity of non-anastomotic pseudoaneurysms (PSAs) in reconstructive vascular surgery. This information is relevant to this specific journal as it contributes to the understanding of vascular surgery complications and the significance of post-operative screening. The paper's focus on the role of imaging techniques in diagnosis and treatment aligns with the journal's interest in advancements in medical imaging and vascular surgery. Additionally, the emphasis on timely detection and management of pseudoaneurysms(PSAs) is of clinical importance, making it suitable for publication in this journal.